Abatacept reduces disease activity of rheumatoid arthritis independently of modulating anti-citrullinated peptide antibody production. Issue 2 (2nd April 2020) - Yamada, Hisakata; Tsuru, Tomomi; Otsuka, Takeshi; Maekawa, Masayuki; Harada, Hiroshi; Fukuda, Takaaki; Tsukamoto, Hiroshi; Maeyama, Akira; Yoshizawa, Shigeru; Wada, Ken; Nakashima, Yasuharu; Shono, Eisuke; et al.
Abstract: Abatacept may exert its clinical effect on rheumatoid arthritis (RA) by suppressing anti-cyclic citrullinated peptide (CCP) antibody production. This study was undertaken to test this hypothesis by examining the changes of disease activity of RA and anti-CCP antibody levels over time after starting abatacept. Sixty Japanese RA patients who started abatacept were included in this multicenter, prospective observational study. Simple Disease Activity Index (SDAI) and anti-CCP antibody levels were evaluated at 12, 24, and 52 weeks. The mean SDAI score significantly decreased within 12 weeks after starting abatacept and was maintained thereafter. On the contrary, the mean anti-CCP antibody levels did not change until 52 weeks. At the individual level, there were substantial changes of anti-CCP antibody levels, but these were not correlated with the changes of disease activity at any time points. Thus, abatacept reduces the disease activity of RA independently of modulating anti-CCP antibody production.